1995
DOI: 10.1093/clinids/20.4.924
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Treatment for Chancroid in Rwanda Is Not Related to Human Immunodeficiency Virus Infection: In Vitro Resistance of Haemophilus ducreyi to Trimethoprim-Sulfamethoxazole

Abstract: A comparative open study was performed to evaluate the efficacy of single doses of ciprofloxacin (500 mg) and trimethoprim-sulfamethoxazole (TMP-SMZ; 640 mg/3,200 mg) for the treatment of culture-proven chancroid. Clinical cure or improvement was observed 7 days after treatment in 32 (76.2%) of the 42 patients who received ciprofloxacin and 21 (52.5%) of the 40 patients who received TMP-SMZ (P = .04). Cultures for one (4.5%) of 22 patients not cured with ciprofloxacin and 16 (59.3%) of 27 patients not cured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Worldwide, several isolates with intermediate resistance to either ciprofloxacin or erythromycin have been reported; thus single dose ciprofloxacin and the shorter (five days) regimen of erythromycin may not be effective, as has been reported by teams in Rwanda and Malawi. 46,47 However, a double-blind randomised controlled trial conducted in Nairobi showed comparable cure rates for single dose ciprofloxacin (92%) and the standard seven-day course of erythromycin (91%). 44…”
Section: Recommended Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, several isolates with intermediate resistance to either ciprofloxacin or erythromycin have been reported; thus single dose ciprofloxacin and the shorter (five days) regimen of erythromycin may not be effective, as has been reported by teams in Rwanda and Malawi. 46,47 However, a double-blind randomised controlled trial conducted in Nairobi showed comparable cure rates for single dose ciprofloxacin (92%) and the standard seven-day course of erythromycin (91%). 44…”
Section: Recommended Regimensmentioning
confidence: 99%
“…found that HIV and the degree of immunosuppression as measured by CD4 counts had no effect on bacteriologic and clinical outcomes, and that treatment failures were entirely attributable to resistance of H. ducreyi to TMP-SMX. 46 CDC recommends that “since data on therapeutic efficacy with the recommended ceftriaxone and azithromycin regimens among patients infected with HIV are limited, those regimens should be used among persons known to be infected with HIV only if follow-up can be assured”. 2 Others have concluded that azithromycin should be avoided in co-infected patients.…”
Section: Special Considerationsmentioning
confidence: 99%
“…The disease has generated renewed interest because of its well-established capacity to amplify the transmission of human immunodeficiency virus (HIV) infection, [1][2][3] and the organism's emerging resistance to drugs. [4][5][6][7] Recent epidemiologic studies have implicated genital/anogenital ulcer disease as an important cofactor for the acquisition and transmission of HIV during sexual intercourse. The identification of such modifiable cofactors for HIV transmission has important implications for control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Although atypical presentations of chancroid in HIV-infected persons were initially reported [16,17], subsequent studies have shown little difference in the clinical course and response to antibiotics between HIV-infected and HIV-seronegativepersons [18][19][20]. The histopathology of chancroid in HIV-infected and HIV-seronegative persons is similar [11,21].…”
mentioning
confidence: 98%